Comparing Outcomes of Airway Changes and Risk of Sleep Apnea after Bimaxillary Orthognathic Surgery and Mandibular Setback Surgery in Patients with Skeletal Class III Malocclusion: A Systematic Review and Meta-Analysis - Safi, Mehrnaz (2021)
Objective: To compare the airway changes and risks of sleep apnea after the bimaxillary orthognathic surgery and mandibular setback surgery in the growing patients with skeletal Class III malocclusion. Material and Methods: MEDLINE, PubMed, Cochrane Library, Embase, ISI, Google scholar have been utilized as the electronic databases for performing systematic literature between 2010 to August 2020. The quality of the included studies has been assessed using MINORS. Meta-analysis was performed using Stata 16 software. Results: In electronic searches, a total of 218 potentially relevant abstracts and topics have been found. Finally, 23 papers met the criteria defined for inclusion in this systematic review. The mean difference of upper airway total volume changes between before and after surgery was (MD = 1.86 cm3 95% CI 0.61 cm3-3.11 cm3; p= 0.00) among 14 studies. This result showed that after Mandibular Setback Surgery, there was a statistically significant decrease in the upper airway volume. Conclusion: Class III Patients who undergo bimaxillary surgery show no other significant difference in airways volume after surgery than patients in Class III who undergo mandibular setback alone.